Improvements in closed-section wind-tunnel beamforming experiments of acoustic sources distributed along a line - Amaral, Filipe Ramos do; do Carmo Pagani Junior, Carlos [UNESP]; de Medeiros, Marcello Augusto Faraco (Elsevier, 2019)
Phased-array microphone techniques are widely used tools for the measurement and analysis of aeroacoustic noise sources. Nevertheless, beamforming results of sources distributed along a line, such as airfoil trailing-edge and slat, have not been entirely understood. This paper investigates the performance of beamforming methods in representing sources distributed along a line and estimating their spectral level. Conventional beamforming and the deconvolution techniques DAMAS and CLEAN-SC were employed for both synthetic and physical sources. The physical source is the slat of an MD30P30N high-lift model tested in a closed-section wind-tunnel with array microphones mounted flush to the tunnel wall. The synthetic source consisted of a large number of uncorrelated aligned monopole point sources. DAMAS was found to be the most accurate approach for both synthetic and physical test cases. The physical source results were not as accurate as the synthetic source ones, nevertheless, they were substantially improved by array shading and by an acoustic treatment (foam coating) on the working section walls. The most effective array shading methodology was based on the mean coherence level of each microphone, here referred to as CW (Coherence Weighting shading).
Keywords: Acoustic treatment; Aligned acoustic sources; Array shading; Beamforming; CLEAN-SC; DAMAS; Reverberation